Agroindustrial Byproducts for the Generation of Biobased Products: Alternatives for Sustainable Biorefineries - Philippini, Rafael Rodrigues; Martiniano, Sabrina Evelin; Ingle, Avinash P.; Franco Marcelino, Paulo Ricardo; Silva, Gilda Mariano; Barbosa, Fernanda Gonçalves; dos Santos, Júlio César; da Silva, Silvio Silvério (Frontiers in Energy Research, 2020)
The integrated approach in biorefinery mainly involves the utilization of various agroindustrial byproducts as raw materials for the production of several biobased products like biofuels, bioenergy, and other high-value chemicals. Biofuels are the backbone of biorefineries, however, production of value-added biomolecules such as biopigments, biopolymers, biosurfactants, nutritional yeast, etc. have been atracting a great attention. The production of these biomolecules using traditional approaches have been extensively studied in last few years due to their promising application in different industries such as chemical, food/feed, and pharmaceutical for the development of novel products for mankind. Moreover, the production of such biomolecules using lignocellulosic, starchy and some other agroindustrial byproducts is still not fully explored. Hence, there is a huge scope in the development of sustainable biorefining approaches to make the technology cost-effective. The lignocellulosic biomasses usually used in biorefineries are mainly composed of cellulose, hemicellulose, and lignin, whereas starchy materials, besides starch, usually contain, protein, lipids and some micronutrients. The processing of these biomasses through successive steps like pretreatments, enzymatic hydrolysis and fermentation is essentially required to obtained final biobased products. Considering certain bottlenecks of above-mentioned conventional biorefineries approaches, new technologies have been proposed for the improved pretreatment of biomass and efficient enzymatic hydrolysis in order to minimize the concentration of toxic inhibitors in resulting hydrolysate. In this review, we highlighted on different agroindustrial byproducts and their applications for the production of valuable biorefinery products.